The Ability of The Adaptation Process According to Callista Roy's Theory is Related to Work Stress in Nurses in The Operating Room - Andriani, Selfiyah; Yuswanto, Tri Johan Agus; Sepdianto, Tri Cahyo; Anjaswarni, Tri (JURNAL INFO KESEHATAN, 2024)
Nurses in the operating room feel that they lack concentration in carrying out surgery because fatigue during emergency operations can result in increased work stress. The process of adaptation is a way that affects behavior in managing stress. The purpose of the study was to prove that there is a relationship between the ability of the adaptation process according to Callista Roy's theory in nurses with work stress in the operating room of Mardi Waluyo Hospital Blitar. This research method is quantitative using a cross-sectional design. The study sample was 28 nurses in the operating room with the total sampling technique. The independent variable of adaptability of the adaptation process was measured with the questionnaire sheet and the dependent variable of work stress was measured with the DASS 42 questionnaire sheet. Data analysis using Spearman test. The research results show that the ability of the adaptation process was mostly moderate in 17 people (60.7%) and work stress was almost half that of normal stress in 12 people (42.9%). The conclusion is there is a significant relationship between the ability of the adaptation process and nurses' work stress with a p-value of 0.001≤0.05 meaning that there is a significant relationship between the ability of the adaptation process with work stress in nurses in the operating room, the direction of the relationship from r count -0.577* is strongly correlated with the direction of negative relationships, meaning that the increasing adaptability the lower the level of work stress.